Intervention to Increase the Motivation to Learn Mathematics for Children Aged 9–13 Years at Rptra X, West Jakarta - Salvezza, Sheila; L.C, Luh Gde Devi; Diyanka, Glenda; Wati, Linda (Devotion : Journal of Research and Community Service, 2025)
Mathematics learning motivation in elementary school-aged children is an important aspect in supporting their academic achievement. This community service activity aims to improve mathematics learning motivation in children aged 9–13 years through an intervention program based on educational activities at RPTRA X, West Jakarta. As an initial stage, a pre-test was conducted using the Elementary Motivation Scale (ESMS), which had been adapted into Indonesian and validated by experts, to measure learning motivation in reading, writing, and mathematics. The pre-test was conducted on April 13 and 26, 2025, and showed that mathematics learning motivation had the lowest score compared to the other two domains. Based on these results, the intervention program was designed based on Self-Determination Theory (SDT), with an emphasis on enhancing autonomy and using extrinsic motivation through giving rewards as a form of positive reinforcement. The intervention was carried out in four sessions on May 17–18 and May 24–25, 2025, using participatory and contextual approaches to enhance mathematics learning motivation. The evaluation was conducted through a post-test on May 25 and 31, 2025. The analysis focused on 21 children who consistently participated in all activities. The results showed a significant increase in mathematics learning motivation scores, indicated by a decrease in the number of low-motivation children from 15 to 2. These findings indicate that educational activity-based interventions and the application of SDT principles can have a positive impact on improving children's mathematics learning motivation in the RPTRA environment.